Community-Acquired Respiratory Distress Syndrome Toxin: Unique Exotoxin for M. pneumoniae - Su, Xiaoling; You, Xiaoxing; Luo, Haodang; Liang, Keying; Chen, Li; Tian, Wei; Ye, Zufeng; He, Jun (Frontiers in Microbiology, 2021)
Mycoplasma pneumoniae often causes respiratory disease in humans, particularly atypical pneumonia and community-acquired pneumonia in children and adults. It is often exacerbated by co-infection with other lung diseases such as asthma, bronchitis, chronic obstructive pulmonary disorder, e. g. and M. pneumoniae can often be detected in patients with asthma. CARDS TX is the only exotoxin produced by M. pneumoniae and has been extensively studied for its ADP-ribosyltransferase activity and cellular vacuolization properties, activating of inflammatory vesicles leading to release of inflammatory factors as well as causing cell swelling, nuclear lysis, mucus proliferation, and cell vacuolization. By binding to the receptor, CARDS TX opens the door to enter the cell and is then reverse transported to the endoplasmic reticulum to exert its pathogenic effects. In this review, we focus on the structural features, functional activity, distribution and receptors, mechanism of cell entry and inflammatory response of CARDS TX. According to the overall analysis and elaboration of CARDS TX, this review will provide a basis for exploring the common properties among related bacterial toxins and provide a theoretical basis for further investigation of the mechanism of infection between M. pneumoniae and host cells and the development of antibacterial drugs and vaccines targeting M. pneumoniae.